Research on the driving force model of internet public opinion based on system dynamics - Feng CAO; Zhenji ZHANG; Xiaolan GUAN (Dianxin kexue)
Internet public opinion,as a reflection of social public opinion in the internet space,in turn affects the development process of social entity events.Improving the ability to deal with online public opinion has become an important task for party committees and government departments at all levels.The rules and characteristics of the spread of online public opinion were analyzed,system dynamics was used to analyze the driving factors of the ecological spread of online public opinion,the relationship between factors was analyzed through causal loop diagrams,and a model of the driving force of online public opinion was established.Finally,the model was simulated and analyzed,in order to put forward suggestions for actively managing the spread of online public opinion.